MODERN METHODS OF TREATMENT OF PATIENTS WITH HIGH-GRADE MYOPIA - Usmanova Tulganoy Jaloliddinovna; Jaloliddinov Davronbek Lutfiddin ugli (Galaxy International Interdisciplinary Research Journal, 2022)
This review article examines modern views on etiological factors, the pathogenesis of complications and the influence of climatogeographic conditions on the progression of myopia and modern methods of treatment.